Preservation of Local Culture Art Wayang Topeng Malangan In Padepokan Topeng Asmarabangun Art - Amanda Ruziana Putri Duanta (Ridwan Institute, 2021)
The results of culture and civilization need to be preserved in accordance with the current situation and conditions as well as changing circumstances. Wayang topeng Malangan is one of the folk arts of the Malang area which is very famous for its local elements. This research was conducted in Dusun Kedungmonggo, Karangpandan Village, Pakisaji, Malang. The approach used in this study is a qualitative approach with data obtained through observation, interviews and documentation. The type of research used is phenomenology